Β‐amyloid context intensifies vascular smooth muscle cells induced inflammatory response and de‐differentiation. Issue 3 (1st April 2013) - Vromman, Amélie; Trabelsi, Nesrine; Rouxel, Clotilde; Béréziat, Gilbert; Limon, Isabelle; Blaise, Régis
1‐40